ALK ligand ALKAL2 potentiates MYCN‐driven neuroblastoma in the absence of ALK mutation. (7th January 2021) - Borenäs, Marcus; Umapathy, Ganesh; Lai, Wei‐Yun; Lind, Dan E; Witek, Barbara; Guan, Jikui; Mendoza‐Garcia, Patricia; Masudi, Tafheem; Claeys, Arne; Chuang, Tzu‐Po; El Wakil, Abeer; Arefin, Badrul; et al.
Abstract: High‐risk neuroblastoma (NB) is responsible for a disproportionate number of childhood deaths due to cancer. One indicator of high‐risk NB is amplification of the neural MYC ( MYCN ) oncogene, which is currently therapeutically intractable. Identification of anaplastic lymphoma kinase (ALK) as an NB oncogene raised the possibility of using ALK tyrosine kinase inhibitors (TKIs) in treatment of patients with activating ALK mutations. 8–10% of primary NB patients are ALK‐positive, a figure that increases in the relapsed population. ALK is activated by the ALKAL2 ligand located on chromosome 2p, along with ALK and MYCN, in the "2p‐gain" region associated with NB. Dysregulation of ALK ligand in NB has not been addressed, although one of the first oncogenes described was v‐sis that shares > 90% homology with PDGF. Therefore, we tested whether ALKAL2 ligand could potentiate NB progression in the absence of ALK mutation. We show that ALKAL2 overexpression in mice drives ALK TKI‐sensitive NB in the absence of ALK mutation, suggesting that additional NB patients, such as those exhibiting 2p‐gain, may benefit from ALK TKI‐based therapeutic intervention. SYNOPSIS: ALK receptor tyrosine kinase (RTK) is aberrantly activated in childhood cancer neuroblastoma (NB), acting in concert with the neural MYC (MYCN) oncogene. As shown here, the recently‐identified ALK ligand ALKAL2 is sufficient to drive ALK‐dependent NB development, irrespective of oncogenic mutations. ALKAL2 ligand stimulates ALK RTK signaling in human NB cells, as measured by RNA‐Seq, global proteomics and phospho‐proteomics. ALK F1178S gain‐of‐function mutation cooperates with MYCN to drive NB in mice. Transgenic ALKAL2 increases MYCN‐driven NB in the presence of wild‐type ALK. ALKAL2‐driven neuroblastoma is sensitive to ALK inhibitor treatment. Abstract : ALKAL2 misregulation facilitates ALK receptor tyrosine kinase signaling and drives ALK‐dependent cancer irrespective of oncogenic mutations.